Foreign ownership as a neglected factor in regions’ smart specialisation exports - Nazarczuk, Jarosław M.; Umiński, Stanisław; Jurkiewicz, Tomasz (Journal of Business Economics and Management, 2020)
A region can internationalise in various ways. The question is what type of internationalisation at regional level can be regarded as “smart” and what role should be played in it by foreign owned entities (FOEs)? The paper aims at identifying the role played by FOEs in NUTS-2 smart specialisations’ (SS’s) internationalisation through exports. With the use of a set of PCSE regressions, the paper depicts the role of FOEs in creating SS-compliant exports against the background of their influence on total regional exports. The obtained results proved the positive role of FOEs in regional exports per se and SS-compliant exports. Yet, FOEs differed substantially, as compared to indigenous entities, in terms of product/regional specialisation and technological advancement. The findings imply the importance of FOEs’ embeddedness in regions’ economies and possibility of their incorporation in creating or enhancing regional comparative advantages. The paper contributes by: (i) providing empirical verification of one of the aspects of SS strategy which is exports and establishing comprehensive insight into the evaluation of SS, (ii) depicting the role of FOEs in generating SS-compliant exports, (iii) proposing a set of measures to be used in the extended empirical evaluation of SS consequences in the sphere of exports.